A Straightforward Route to Aromatic Excited States in Molecular Motors that Improves Photochemical Efficiency. Issue 6 (28th February 2019) - Wang, Jun; Oruganti, Baswanth; Durbeej, Bo
Abstract: The many successful efforts to optimize the thermal steps that are part of the reaction cycles of most light‐driven rotary molecular motors have not been followed by studies providing a similarly detailed understanding of how the efficiency of the photochemical steps that actually power the motors can be improved. Against this background, we herein use computational methods to investigate the merits of an approach to increase the quantum yields of E / Z ‐photoisomerization‐based motors by enabling one of their two moieties to become aromatic in the photoactive excited state. Through quantum chemical calculations, a straightforward route to excited states of this type is found for motors where one moiety can be transformed into an aromatic anion by an electron donor at the other moiety. Furthermore, through molecular dynamics simulations, motors operated in such excited states are indeed predicted to be much more efficient than similar motors operated in the absence of excited‐state aromaticity. Abstract : Make it spin, baby ! A straightforward route to making light‐driven rotary molecular motors exhibit excited‐state aromaticity (ESA) is identified from quantum chemical calculations and shown by non‐adiabatic molecular dynamics simulations to hold great promise in improving the photochemical efficiency of these systems.